LOCAL SEISMIC RESPONSE AND EARTHQUAKE VULNERABILITY ZONING AROUND THE BOGOR FAULT, KEPAHIANG REGENCY, BENGKULU - Nurul Apriyanti; Muchammad Farid; Arif Ismul Hadi; Hana Raihana; Arya Putra Anggi; Clora Ulandari (Universitas Mataram, 2026)
Kepahiang Regency, Bengkulu Province, is located in the active tectonic zone of the Sumatran Fault System (Musi Segment), with the Bogor Fault running near residential areas, potentially increasing the risk of local earthquakes. This study aims to analyze local seismic response and map earthquake-vulnerability zones along the Bogor Fault using microseismic measurements from 40 observation points. This analysis integrates the parameters f0, A0, SVI, PGA, GSS, and Vs to evaluate the structural influence of the Bogor Fault on seismic response and earthquake vulnerability. The results show a range of values for f₀ of 1.64–17.97 Hz, A₀ of 2.15–9.15, SVI of 0.91–35.52, PGA 0.12–0.41 g, GSS 1.01 × 10⁻⁵–1.97 × 10⁻⁴, and Vs 183–2700 m/s, with location classes ranging from SA to SE according to SNI 1726:2019. Areas with low Vs values exhibit higher SVI, PGA, and GSS values, indicating stronger seismic amplification and greater potential for deformation. The distribution of these parameters aligns with the orientation of the Bogor Fault, suggesting a structural influence on the local seismic response. A comprehensive analysis of f0, A0, SVI, PGA, GSS, and Vs identified three vulnerability zones: high vulnerability along the central-to-northeastern corridor of the Bogor Fault and low vulnerability in the western and southwestern sectors. Microzonation mapping resulted in categorizing the study area into low-, moderate-, and high-vulnerability zones. This study revealed that the level of earthquake vulnerability in Kepahiang is largely determined by geological conditions, including the presence of faults, which can guide earthquake hazard mitigation efforts and the development of risk-based spatial planning.